2019
DOI: 10.1186/s12875-019-1034-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of accreditation impact in general practice – a qualitative study among general practitioners and their staff

Abstract: BackgroundAccreditation is a widespread tool for quality management in health care. However, there is lack of research on the impact of accreditation, particularly in general practice. This study explores how general practitioners and their staff experienced the impact of a mandatory accreditation program in Denmark.MethodsQualitative interviews with general practitioners and staff from 11 clinics. The respondents were interviewed twice: during preparation and after the survey visit. The interviews were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…With respect to the research questions, it was found that preparing for accreditation went hand-in-hand with increased psychosocial risks, such as increased job demands and work pace, conflicting information, and perceived strain. Such findings support evidence from previous observations regarding the negative impacts of accreditation, which include increased workload (Touati and Pomey, 2009;El-Jardali et al, 2014), increased stress levels (Kousgaard et al, 2019), and use of resources (Brubakk et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With respect to the research questions, it was found that preparing for accreditation went hand-in-hand with increased psychosocial risks, such as increased job demands and work pace, conflicting information, and perceived strain. Such findings support evidence from previous observations regarding the negative impacts of accreditation, which include increased workload (Touati and Pomey, 2009;El-Jardali et al, 2014), increased stress levels (Kousgaard et al, 2019), and use of resources (Brubakk et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The nature of accreditation is to assess the performance of healthcare facilities through an external inspection process, using a defined set of standards. When comparing accredited and non-accredited ones, accreditation has been found to support the promotion of patients' health and safety (Shaw et al, 2010), improve the quality of healthcare services (Greenfield and Braithwaite, 2008;O'Beirne et al, 2013;Shaw et al, 2014;Bogh et al, 2016), encourage organizational change (Kousgaard et al, 2019), and allow professional development (Greenfield and Braithwaite, 2008). Furthermore, previous research has shown that accreditation can have positive effects on the quality of healthcare management and leadership (El-Jardali et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target intervention population for 18 studies were doctors, and predominantly primary care providers/general practitioners. 26,28,34,35,37,39,46,47,49,50,55,56,[58][59][60][65][66][67] To be included and eligible to participate in an intervention, primary care providers often needed to treat a specific subset of patients in their practice. For example, Presseau et al focused on general practitioners who provided care to patients with type 2 diabetes across 44 general practices through a national cohort study.…”
Section: Provider and Health Setting Characteristicsmentioning
confidence: 99%
“…Accreditation may affect general practice in very different ways. Despite several examples of positive impact, the results suggest that it is difficult to design a mandatory accreditation programme for general practice in which most professionals experience that the benefits of accreditation equal the resources used in the process (Kousgaard et al, 2019). The accredited healthcare setting implement quality care and patients’ safety practice better than non-accredited facilities.…”
Section: Introductionmentioning
confidence: 99%